2018
DOI: 10.1111/jcmm.13525
|View full text |Cite
|
Sign up to set email alerts
|

ETS1 and SP1 drive DHX15 expression in acute lymphoblastic leukaemia

Abstract: DHX15 plays a role in leukaemogenesis and leukaemia relapse. However, the mechanism underlying the transcriptional regulation of DHX15 in ALL has not been elucidated. Our present study aimed to explore the functional promoter region of DHX15 and to investigate the transcription factors controlling the transcription of this gene. A luciferase assay performed with several truncated constructs identified a 501‐bp region as the core promoter region of DHX15. Site‐directed mutagenesis, electrophoretic mobility shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Our results also showed that ETS-1 site mutation resulted in more activity reduction compared NF-kB, NF-Y, and ElK-1 sites, as ETS-1 site is overlapped with Sp1 proximal site, mutation of ETS-1 might partially affected the Sp1 activity. In previous studies, the cooperation of Sp1 and ETS-1 in gene regulation was observed [29,30]. Therefore, ETS-1 role can be expected in the Sp1-mediated TMBIM6 expression.…”
Section: Discussionmentioning
confidence: 80%
“…Our results also showed that ETS-1 site mutation resulted in more activity reduction compared NF-kB, NF-Y, and ElK-1 sites, as ETS-1 site is overlapped with Sp1 proximal site, mutation of ETS-1 might partially affected the Sp1 activity. In previous studies, the cooperation of Sp1 and ETS-1 in gene regulation was observed [29,30]. Therefore, ETS-1 role can be expected in the Sp1-mediated TMBIM6 expression.…”
Section: Discussionmentioning
confidence: 80%
“…Abnormal Sp1 expression and activation are considered to promote human cancer initiation and progression, including leukemia. Evidence demonstrates that Sp1 modulates drug resistance of LSCs by regulating survivin expression [12], and that Sp1 drives DHX15 expression in acute lymphoblastic leukemia [13]. Nevertheless, the role of SP1 driving FUT4 transcription in AML LSCs has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…DHX15 has been shown to function in multiple biological processes, including pre-mRNA splicing ( Yoshimoto et al., 2009 ), ribosome assembly, and biogenesis ( Chen et al, 2014 ; Memet et al, 2017 ; Studer et al, 2020 ). A few studies suggest that DHX15 contributes to carcinogenesis in leukemia ( Chen et al, 2018 ), breast cancer ( Lin et al, 2009 ), prostate cancer ( Jing et al, 2018 ), and hepatocellular carcinoma ( Xie et al, 2019 ) and acts as a tumor suppressor gene in glioma ( Ito et al, 2017 ) and gastric cancer ( Xiao et al, 2016 ). Importantly, we and other groups have shown that DHX15 is an RNA virus sensor through binding double-stranded RNA (dsRNA) from RNA virus and induces the production of IFN-I and proinflammatory cytokines in dendritic cells (DCs) in response to dsRNA and RNA viruses in vitro ( Lu et al, 2014 ; Mosallanejad et al, 2014 ; Pattabhi et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%